Interest of systematic screening of pheochromocytoma in patients with neurofibromatosis type 1. Issue 4 (October 2016) - Képénékian, Lori; Mognetti, Thomas; Lifante, Jean-Christophe; Giraudet, Anne-Laure; Houzard, Claire; Pinson, Stéphane; Borson-Chazot, Françoise; Combemale, Patrick
Abstract : Objective: Pheochromocytoma (PHEO) may occur in 0.1–5.7% of patients presenting with a neurofibromatosis type 1 (NF1). Current recommendations are to explore only symptomatic patients. The objective of the study is to evaluate the prevalence and the interest of a systematic PHEO screening in this population. Design: A prospective study in a French tertiary center including consecutive NF1 patients older than 18 years. Methods: A systematic screening combining abdominal imaging and urinary fractionated metanephrines was proposed. In case of positivity of one or both exams, 123 I-metaiodobenzylguanidine scintigraphy or [ 18 F]-fluoro-dihydroxyphenylalanine PET imaging was performed. The diagnosis of secreting PHEO was retained in case of elevated urinary metanephrines associated with positive scintigraphy and non-secreting PHEO when urinary metanephrines were normal with a positive scintigraphy. Results: Between January 2014 and August 2015, 234 patients were included and 156 patients (66.7%) completed both exams. In these 156 patients, 12 PHEOs were diagnosed, representing a prevalence of 7.7%. Of these, six PHEOs were secreting, with only two symptomatic patients. The tumor size of these PHEOs were bigger than that of non-secreting PHEO (25.2 ± 6.6 vs 14 ± 6.9 mm, P = 0.0165). One lesion was bilateral. Mean metanephrine and normetanephrine levels were 3.2 ± 2.6N and 2.8 ± 1N respectively. Three patients underwent surgery. The six patients with non-secreting PHEO were asymptomatic. One of them had bilateral lesion and one underwent surgery. Conclusions: PHEO in NF1, whether or not secreting, are mostly asymptomatic. The current strategy to explore only symptomatic patients leads to an underestimation of prevalence with the risks inherent to the existence of an unrecognized PHEO.